Two-dimensional organic cathode materials for alkali-metal-ion batteries - Zhang, Chao; Lu, Chenbao; Zhang, Fan; Qiu, Feng; Zhuang, Xiaodong; Feng, Xinliang (Journal of Energy Chemistry, 2018)
With the increasing demand for large-scale battery systems in electric vehicles (EVs) and smart renewable energy grids, organic materials including small molecules and polymers utilized as electrodes in rechargeable batteries have received increasing attraction. In recent years, two-dimensional (2D) organic materials possessing planar layered architecture exhibit optional chemical modification, high specific surface area as well as unique electrical/magnetic properties, which have been emerging as the promising functional materials for wide applications in optoelectronics, catalysis, sensing, etc. Integrating with high-density redox-active sites and hierarchical porous structure, significant achievements in 2D organic materials as cathode materials for alkali-metal-ion batteries have been witnessed. In this review, the recent progress in synthetic approaches, structure analyses, electrochemical characterizations of 2D organic materials as well as their application in alkali-metal-ion batteries containing lithium ion battery (LIB), lithium sulfur battery (LSB), lithium air battery (LAB) and sodium ion battery (SIB) are summarized systematically, and their current challenges including cycling stability and electron conductivity for cathode materials in battery fields are also discussed.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Alkali-metal-ion battery; Cathode; Organic material; Two-dimensional